State’s Management of Belief and Religious Activities according to Vietnam law and role in the direction of cultural activities - Vu, Van Hong (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2024)
Vietnam’s innovation process, which started in 1986, has created many changes in the country's economic, political, and cultural life while changing the state’s behaviour regarding beliefs and religions. According to the Law on Belief and Religion (2016), many forms of beliefs are recognised, and many religions coexist in Vietnam and have a role in the direction of cultural activities. The Vietnam State also respects the people’s right to freedom of belief and religion. The topic of this study is to focus on clarifying the diversity in people’s beliefs and religious activities as well as the recognition by the State’s legal documents on the diversity of beliefs, many religious organisations as well as the people’s freedom of beliefs, and religion when the country innovation. In this context, information about different types of beliefs and religions, diversity in belief and religious activities, and number of followers will be provided. Then, there is the legal basis of people’s freedom of belief and religious activities; regulations on the organisation and operation of religious organisations will be considered and evaluated. Limitations and shortcomings in religious activities will be discussed; some orientation issues for the state management of beliefs and religions were raised. This study aims to evaluate the positive changes in the State’s belief and religion policy and propose some solutions to improve the State’s management policy and law on belief and religion. This study has important implications for the State to continue to have policies to manage and promote the people’s diversity in belief and religious activities.